The undergraduate 'corridor of uncertainty': teaching core concepts for managing clinical uncertainty as the 'special technique' of general practice. Issue 2 (4th March 2022) - Cooper, Maxwell; Sornalingam, Sangeetha; Jegatheesan, Menaka; Fernandes, Carl
ABSTRACT: McWhinney's first principle of family medicine states that GPs 'are committed to the person rather than to a particular body of knowledge, group of diseases, or special technique'. While indeed committed to the person, we propose that the 'special technique' of general practice exists in the form of core clinical concepts for managing uncertainty (e.g. time as a tool, therapeutic examination, safety netting and doctor as drug). Managing clinical uncertainty calls for GPs (and trainees) to operate in a 'corridor of uncertainty', a cricketing analogy where the batter is unsure whether to play a defensive or attacking shot. For students to recognise and value these concepts requires longitudinal learning and simulation. Here we describe a GP module at Brighton medical school where core concepts are 'drip fed' through small group sessions across year 4. Formative simulated surgeries constitute a 'corridor of uncertainty' where simulated patients drive students into using concepts in practice (e.g. through shared management plans). Although recognised in postgraduate training, these concepts should be taught formally within the undergraduate curriculum. Doing so helps students distinguish general practice from hospital generalism and prepares them for clinical placements in general practice. These concepts are inherently 'soft' and founded upon the GP paradigm of understanding medicine. In the eyes of the specialist, they risk being unacknowledged, misinterpreted as ignoring guidelines or, worse still, as bad medicine. Soft core concepts constitute the tools to prepare students for managing clinical uncertainty and serve to inscribe the art of medicine within the undergraduate curriculum.